Pengaruh Job Satisfaction Dan Work Motivation dalam Meningkatkan Kinerja Perilaku Kewarganegaraan Organisasi Pada Pegawai Dinas Lingkungan Hidup dan Kehutanan Provinsi Gorontalo - Bhella Pratiwi Laiko; Heldy Vanni Alam; Andi Yusniar Mendo (MES Management Journal, 2025)
This study aimed to determine whether Job Satisfaction and Work Motivation towards Organizational Citizenship Behavior (OCB) simultaneously affect Employees of the Environmental and Forestry Agency of Gorontalo Province. The data collection technique employed in this study was a questionnaire with a population of all Civil Servants (PNS) of the Environmental and Forestry Agency of Gorontalo Province or 77 employees in total. In the meantime, the samples were determined using total sampling due to the population was relatively small. The analytical test tool used in testing this research was multiple linear regression. The data analysis method used the SPSS 26 application. Based on the findings, the multiple refression analysis test result indicated that the simultaneous test of the variables of Job Satisfaction and Work Motivation had a moderate (not strong) effect on Organizational Citizenship Behavior. In detail, the effect recorded was 0.758 or 75.8%. Meanwhile, the remaining 0.24.2 or 24.2% was affected by other variables not examined in the study.